2019
DOI: 10.1108/rpj-10-2018-0278
|View full text |Cite
|
Sign up to set email alerts
|

A design for additive manufacturing case study: fingerprint stool on a BigRep ONE

Abstract: Purpose This paper aims to present new qualitative and quantitative data about the recently released “BigRep ONE” 3 D printer led by the design of a one-off customized stool. Design/methodology/approach A design for additive manufacturing (DfAM) framework was adopted, with simulation data iteratively informing the final design. Findings Process parameters can vary manufacturing costs of a stool by over AU$1,000 and vary print time by over 100 h. Following simulation, designers can use the knowledge to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A similar growth in medical research using AM technology was noted in a systematic review of surgical orthopaedic guides [48], with an increase in research observed shortly after 2009 when key FFF patents expired. FFF is an extrusion process also known as Fused Deposition Modelling (FDM), and has become synonymous with affordable desktop machines, although there are also high-end commercial varieties of this technology [44,45]. A broader systematic review of 3D printing across medical fields confirmed this trend [49], and while little evidence exists to correlate the patent expiry with the increased use of FFF within research, the results from this study align with recent systematic reviews that indicate a rapid growth in medical research utilising 3D printing within the last ten years [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…A similar growth in medical research using AM technology was noted in a systematic review of surgical orthopaedic guides [48], with an increase in research observed shortly after 2009 when key FFF patents expired. FFF is an extrusion process also known as Fused Deposition Modelling (FDM), and has become synonymous with affordable desktop machines, although there are also high-end commercial varieties of this technology [44,45]. A broader systematic review of 3D printing across medical fields confirmed this trend [49], and while little evidence exists to correlate the patent expiry with the increased use of FFF within research, the results from this study align with recent systematic reviews that indicate a rapid growth in medical research utilising 3D printing within the last ten years [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to Prusa Research (2020) , the RC3 face shield should be quicker to 3D print than the previous RC2 version, which was not found to be true with the settings in this study. This highlights the influence of design for additive manufacturing (DfAM), when a product has been designed for a specific machine or process ( Diegel et al , 2019 ; Novak & O'Neill, 2019 ; Thompson et al , 2016 ), as well as the importance of print settings to optimise production ( Chua & Leong, 2017 ). Yet with the global nature of the maker community, equipped with a broad variety of FFF 3D printers with different capabilities, it was important to provide objective and realistic data aligned with the capabilities that many makers may have, particularly those who may have less experience in modifying machines to print with large nozzles, or modifying slicing settings to get the most out of their machine for a specific design.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the overall course length was limited to 1000mm to represent build plates for large FDM printers such as the BigRep ONE, which features a build plate of 1005mm in both the X and Y dimensions [21]. The algorithm was also limited to a maximum of 10 collections repeating in the Y direction due to the computer graphics hardware requirements to generate this geometry on screen in real-time, with each additional course reducing system performance.…”
Section: User Interfacementioning
confidence: 99%